Vulnerable victims and victimisation within practice and policy in the UK: perspectives from practitioners and academic insights - Bennett, Kirsty; Riley, Laura (Palgrave studies in victims and victimology, 2025)
-- Part I: The Validity of Victimhood: How Social Capital, Identity and Professional pp.1 Perceptions Impact on Experiences of Exploitation -- Chapter 1: Introduction: Reconciling Diverse Perspectives of Contested Concepts -- Chapter 2: Beyond Tokenism: An Intersectional Approach to Understanding Vulnerable Victims with Marginalised Identities -- Chapter 3: Fraud: Unheard Victims & Unseen Harms -- Part II: Systemic Victimisation: How Structural Oppression Retraumatises Vulnerable People -- Chapter 4: The normalisation of transphobic victimisation -- Chapter 5: The Relationship Between the Families of Long-Term Missing Persons and Police Forces in the UK -- Chapter 6: Language Use & Victim Blaming During Sexual Violence Victim/Survivor Interactions in the Criminal Justice System -- Chapter 7: Perpetrators or Victims? The Prevent Duty and the Discourse of “Vulnerability” in UK Counter-Radicalisation Policy -- Part III: Progressing Provision for Vulnerable Victims: Proposals to Enhance Professional Practice and Academic Understanding -- Chapter 8: An Intersectional Lens: Prioritising the Voices and Needs of Criminally Exploited Children Through a “Child First” Framework -- Chapter 9: A Practical Guide to Understanding and Minimising Vulnerability Risks for Black Women in the Criminal Justice System -- Chapter 10: Relationships at Risk: Insights into Impulsivity and Aggression in Victim-Informed Domestic Abuse -- Chapter 11: Supporting victim/survivors through the criminal justice process -- Chapter 12: Secondary victimisation: Victim-blaming, Retraumatisation and the Criminal Justice System -- Chapter 13: Best Rhetoric, Worst Practice? A Critical Consideration of Global Responses to Vulnerable Victims.